Scenario guided policy planning: processes, comparisons, and lessons from East Africa - Muchunguzi, Perez; Ampaire, Edidah L.; Acosta, Mariola; Rutting, Lucas; Tumuhereze, Martin; Mwongera, Caroline; Okiror, John Francis; Asten, Piet J.A. van (2016)
Key messages: Participants in policy processes require constant communication and networking among stakeholders to be able to exploit the available policy windows. The review process requires a dynamic and engaging tool. The robustness of a review tool is one step toward having a good and fruitful review process. Using socio-economic scenarios and quantitative evidence in policy review processes allows policy actors to develop a great body of information in an all-inclusive manner, keeping all stakeholders engaged. This alone, however, does not guarantee success. State and non-state actors need to invest in trust building if the citizenry is to benefit from the fast approaching private-public partnership frameworks. It is beneficial to work on a single policy document that is already under a review or formulation process.